PHASE TRANSITIONS AND VOLUMETRIC PROPERTIES OF CRYOLITE, NA3ALF6: DIFFERENTIAL THERMAL ANALYSIS TO 100 MPA - Dolejš D.; Baker D.R. (My University, 2006)
Cryolite, Na3AlF6, is the most abundant aluminofluoride mineral in highly evolved felsic suites and their pegmatites, but its phase transitions and thermodynamic properties at elevated pressures are unknown. We used a simple modification of the TZM pressure vessel to perform differential thermal analysis of cryolite at high pressures. Temperatures of the (α-β transition are as follows: 559.30 ± 0.23 °C (1 atm), 562.10 ± 0.28 °C (47 MPa), and 567.33 ± 0.23 °C (101 MPa). Cryolite melting temperatures increase as follows: 1011.4 ± 0.2 °C (1 atm), 10 19.2 ± 0.4 °C (50 MPa), and 1028.7 ± 0.4 °C (100 MPa). Both pressure-temperature relationships are linear: (dT/dp)αβ= 78.4 ± 8.4 °C/GPa and (dT/dp)m = 174 ± 12 °C/GPa. Application of the Clapeyron relationship leads to the following volumetric changes: ΔVα-β = 0.089 ± 0.019 J/(mol·bar) and ΔVm = 1.49 ± 0.12 J/ (mol·bar). Despite the significant self-dissociation in the cryolite liquid, melting sensu stricto (without dissociation) dominates the heat and volumetric changes during melting in comparable amounts: 83.3 ± 6.7% ΔHm and 68 ± 15% ΔVm and suggests that the degree of dissociation has no significant effect on the (dT/dp)m. Evaluation of previous and current volumetric data for cryolite polymorphs leads to Vβ1284 = 8.49 ± 0.17 J/ (mol·bar); coefficients for the volumetric thermal expansion in the form of the third-order polynomial equation are: V298 = 7.080 ± 0.012 J/ (mol·bar), a1 = (1.39 ± 0.20)·10-4 K-1, a2 = (-2.15 ± 0.51) ·10-7 K-2, and a3 = (2.68 ± 0.34) ·10-10 K-3. The total (dT/dp)m of cryolite is very similar to that of villiaumite (NaF), whereas ΔVm/Vβ.1284 of cryolite is smaller than for other alkali halides (NaF, NaCl).
Keywords: CRYOLITE; DTA; PHASE TRANSITION; TGA; THERMODYNAMICS